The Plays of Samuel Beckett - Weiss, Katherine (Critical Companions Ser., 2012)
'The Plays of Samuel Beckett' provides a stimulating analysis of Beckett's entire dramatic oeuvre, encompassing his stage, radio and television plays. Ideal for students, this major study combines analysis of each play by Katherine Weiss with interviews and essays from practitioners and scholars.